Efficient dynamic bandwidth allocation algorithm for upstream EPON - Radzi N.A.M.; Din N.M.; Al-Mansoori M.H.; Mustafa I.S.; Sadon S.K. (2023)
In this paper, an efficient dynamic bandwidth allocation (DBA) algorithm based fuzzy logic for upstream Ethernet passive optical networks (EPON) is proposed. The algorithm provides the allotment of bandwidth for inter optical network unit (ONU) and intra ONU. We compared the performance of DBA algorithm based fuzzy logic and DBA algorithm without fuzzy logic in terms of bandwidth utilization and delay. The results shows that the usage of fuzzy logic improve the bandwidth utilization up to 20% and about 50% reduction on the system delay is achieved. 2009 IEEE.